ANALISIS PENGUASAAN KONSEP MAHASISWA PENDIDIKAN FISIKA FKIP UNIVERSITAS JEMBER TENTANG PEMANASAN GLOBAL - Devi Aprilia Nurvirani; Singgih Bektiarso; Sudarti Sudarti (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract This research is a descriptive research. This study aims to identify the mastery of the concepts and attitudes of physics education students at Teacher Training and Education Faculty of Jember University on global warming. The research subjects were 63 students in semester VI physics education in Teacher Training and Education Faculty of Jember University 2018-2019 academic year. Data on mastery of concepts were collected through the provision of written tests of 10 multiple choice questions and 2 description questions, while data on attitudes were collected through questionnaires. The results showed that 1.7% of students mastered the concept of global warming very well, 22.2% of students mastered the concept of global warming well, 63.5% of students mastered the concept of global warming quite well, 3.2% of students mastered the concept of warming global is not good, and 9.5% of students master the concept of global warming is not very good. From the results of the study, it is also known that 36.5% of students have a very good attitude towards the phenomenon of global warming, 50.8% of students have a good attitude towards the phenomenon of global warming, 12.7% of students have sufficient attitudes towards the phenomenon of global warming, and there are no students who have a lack of attitude and are very unfavorable towards the phenomenon of global warming. The conclusions obtained from this study are 1) in general the mastery of the concept of physics education students at Teacher Training and Education Faculty of Jember University about global warming is quite good at percentage 69,05%, and 2) the attitude of students of physics education at Teacher Training and Education Faculty of Jember University to the phenomenon of global warming is good at percentage 83,62%. This reasearch can be used to identify the factors that influence the level of mastery of the concepts and attitudes of physics education students at Teacher Training and Education Faculty of Jember University. So lecturers can determine the right learning for physics education students. Key word: mastery of concept, attitudes, global warming